TINGKAT KESEJAHTERAAN MASYARAKAT DI KAWASAN HUTAN TANAMAN RAKYAT DUSUN TAMPANING DESA PATAMPANUA KECAMATAN MARIORIAWA KABUPATEN SOPPENG (Jurnal Eboni, 2020)
AbstractThis study aims to assess the welfare indicators and to determine the welfare of community at community plantation forest areas. This study was conducted in December 2014 to January 2015, in community plantation forest areas Tampaning Hamlet, Patampanua Village, Marioriawa Subdistrict, Soppeng District. Data collected through observation, documentation and interview (questionnaire). Analysis method used is the analysis of revenue and analysis of cost to determine the amount of income of people in the use of forest products, and the qualitative descriptive analysis that explains the level of welfare were based on eight indicators from Central Agency of Statistics, which includes income, household consumption, state of residence, residence facility, the health of family members, accessibility to health, accessibility to education, and transport services.The results showed that public’s netto revenue by the use of non-timber forest products such as nuts, cocoa, sugar, honey, and livestock are Rp. 470.689.000/person/year and in average is 15.689.633/ person/year. The level of welfare at income indicator are criteria of high, household consumption with criteria of moderate, state of residence in the form of semi-permanent categories, residential facilities with criteria of sufficient, the health of family members with criteria of sufficient, accessibility to health with category of easy, accessibility to education with category of sufficient, and transport services with category of sufficient. Based on the accumulation of eight indicators of wellfare that have been previously studied, the welfare level of community in Tampaning Hamlet is in category of sufficient. The level of welfare in the area of community plantation forest (HTR) is increased if timber forest products can be managed immediately. Allowing timber logging in the area that have not been issued by the local government can help communities to solve the issues related to welfare.